2008
DOI: 10.1097/cad.0b013e32830b5894
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate decreases membrane fluidity and induces apoptosis through tumor necrosis factor receptor 1 in breast cancer cells

Abstract: In recent years, studies with plant compounds have shown both chemotherapeutic and chemopreventive properties. The current study with plant stress hormones (jasmonates) showed growth inhibitory effects in breast cancer cells. Cis-jasmone (CJ) and methyl jasmonate (MJ) inhibited the long-term proliferation of MDA-MB-435 and MCF-7 cells. Cell cycle analysis showed G0/G1 and S-phase arrest with increasing apoptotic population. Cellular signaling studies with MJ showed decreased membrane fluidity and activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…Curiously, several reports still claim the presence of caspase-3 in the breast carcinoma cell line MCF-7 in which this enzyme is supposed to contribute to apoptosis signaling [7][8][9][10][11][12][13][14][15]. This was not only demonstrated indirectly via fluorometric assay systems measuring caspase-3-like activities-that might be also elicited by the closely related caspase-7-but by Western blotting analyses demonstrating directly the presence of this protease in MCF-7 cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Curiously, several reports still claim the presence of caspase-3 in the breast carcinoma cell line MCF-7 in which this enzyme is supposed to contribute to apoptosis signaling [7][8][9][10][11][12][13][14][15]. This was not only demonstrated indirectly via fluorometric assay systems measuring caspase-3-like activities-that might be also elicited by the closely related caspase-7-but by Western blotting analyses demonstrating directly the presence of this protease in MCF-7 cells.…”
mentioning
confidence: 99%
“…Thus, it is puzzling that caspase-3-deficient MCF-7 cells exhibit DNA fragmentation and other apoptotic characteristics following cell death induction as described [7][8][9][10][11][12][13][14][15]. While it is still possible that caspase-3-deficient MCF-7 cells display high molecular weight DNA fragmentation that might be occasionally mistaken for the typical apoptotic DNA fragmentation, the detection of a caspase-3 protein in MCF-7 cells [7,8,11,[13][14][15] with a partially deleted CASP-3 gene is cause for concern. Such discrepant findings may be partially explained by the use of inappropriate antibodies that cross-react with other caspase-3-unrelated proteins in cellular extracts, a phenomenon we have also observed previously (unpublished data).…”
mentioning
confidence: 99%
“…11 Several reports have demonstrated that cyclopentenone moiety-containing molecules such as prostaglandins and clavulones induce apoptosis in different signaling mechanisms. [12][13][14] Jasmonate-derivative compounds, including jasmonic acid (JA) and methyl dihydrojasmonate (MJ), have been reported to inhibit the growth of leukemia cells as well as lung, breast, and prostate cancer cells, and to produce in vivo anticancer activity. 15,16 Different mechanisms have been proposed to explain the anticancer activity of jasmonate derivatives.…”
Section: Silva Et Almentioning
confidence: 99%
“…It has been reported that methyl jasmonate inhibits cell proliferation and induces cell death in various human and mouse cancer cell lines, such as breast, prostate, lung, melanoma, lymphoblastic leukemia and lymphoma cells (1)(2)(3). Methyl jasmonate exhibited selective cytotoxicity to transformed cells while sparing normal blood lymphocytes, even when the latter were part of a mixed population of leukemic and normal cells drawn from the blood of chronic lymphocytic leukemia (CLL) patients (4,5).…”
Section: Introductionmentioning
confidence: 99%